Mixing of Traditional and Modern Forms in Architecture of Sunan Ampel Mosque, East Java, Indonesia - Ashadi Ashadi (Department of Architecture Universitas Muhammadiyah Jakarta, 2017)
The architectural form of Sunan Ampel mosque was alleged that there was mixing of traditional and modern forms. Traditional forms were shown by local forms, while its modern forms were shown by non local forms. This study aimed to understand mixing of traditional and modern forms in architecture of Sunan Ampel mosque. The method used in this study was descriptive, analytical, and interpretive, based on empirical evidence. The steps of analysis and interpretation were as follows. The first step, was opening architectural forms consisting of under cover, side cover, and top cover. The second step, was comparing the architectural forms of Sunan Ampel mosque with the reference of architectural forms. The third step, was analyzing and interpreting that comparing. The results of this study concluded that mixing occurred in architectural form of Sunan Ampel mosque showed domination of traditional forms to modern forms. This study was expected to contribute knowledge about mixing of traditional and modern forms in architecture of mosques in Indonesia, and could position it in global context.